Pengaruh Ekuitas Merek Terhadap Proses Keputusan Pembelian Konsumen : Studi Kasus Bank Muamalat Indonesia Cabang Bandung - Chan, Arianis (Jurnal Administrasi Bisnis, 2010)
Being a pioneer for the sharia bank in Indonesia, Bank Muamalat Indonesia shouldprovide service excellence with increasing brand equity to gain more consumer andto make consumer choosing Bank Muamalat Indonesia.The objectives of this research are to know respondent assessment on brand eq-uity and customer purchase decision process at Bank Muamalat Indonesia BandungBranch and to know the influence of brand equity towards the customerâs decisionmaking process.This research used descriptive survey and explanatory survey method. The re-search population were customer Bank Muamalat Indonesia - Bandung Branch . Thedata were collected by observation technique, interview and questionnaire which un-derwent validity and reliability test. The data analyzed by qualitative analysis uses thecategory determination in the term percentage for each sub variable and for statisticalanalysis uses the Structural Equation Modeling.The results of this research indicate that brand equity of Bank Muamalat In-donesia was high category and also for the customerâs purchase decision makingprocess at Bank Muamalat Indonesia- Bandung Branch was high category too. Brandequity have highest effect on decision making process of customer to purchase, thatmeans the brand equity have better condition can make higher in customerâs purchasedecision making process.Keywords: : brand equity, customer purchase decision making process